Cross-species evidence that nicotine widens the attentional window. - Hahn, Britta (Psychopharmacology, 2021)
Rationale: The ability to spread attention over items or locations is as important for everyday functioning as the ability to focus narrowly. Little is known about neuronal processes involved in broad monitoring, but indirect evidence suggests a role of nicotinic acetylcholine receptors (nAChRs). Objective: The present study tested whether the prototypical nAChR agonist nicotine enhances the ability of humans and rodents to maintain a broad attentional window. Methods: Fifty-three never-smokers wearing a nicotine (7 mg/24 h) or placebo patch performed an attention task requiring detection of stimuli presented randomly in one of four peripheral locations, with a central cue predicting the target location or indicating the need to spread attention over all locations. Nineteen rats performed the 5-choice serial reaction time task requiring detection of stimuli presented randomly in a horizontal array of five locations. Performance after nicotine (0.1 and 0.2 mg/kg) or vehicle administration was analyzed as a function of target location eccentricity. Results: In human subjects, nicotine caused greater reaction time reduction when all locations were monitored than when a single location was cued. In rats, nicotine attenuated the decline in stimulus detections and the increase in omission errors with greater target location eccentricity. Conclusions: The findings represent cross-species evidence that nAChR agonism facilitates the ability to spread attention broadly. This suggests that nAChR hypofunction may be central to broad monitoring deficits as seen, for example, in schizophrenia. The homology of findings between the rodent and the human paradigm contributes to validating a translational strategy for treatment development.